Pengaruh model problem-based learning berbantuan media audio visual terhadap kemampuan berpikir kritis peserta didik - Ningtias, Auliyah Indah; Rohimah, Siti Maryam; Indriyani, Yuni (Karoteh Utama, 2024)
This study aims to analyze whether there is a significant difference in critical thinking skills between students using the Problem-Based Learning (PBL) model assisted by audiovisual media and those using the conventional teaching model. This research employs a quantitative approach with a quasi-experimental method, using a nonequivalent control group design, involving one experimental class and one control class. Data were collected through tests, consisting of pretest and posttest, as well as non-test methods including observation and documentation. Data analysis techniques were performed using normality tests, homogeneity tests, and hypothesis testing with IBM SPSS Statistics 25 software. The results of the hypothesis test on pretest data showed no significant difference in the average critical thinking skills between students in the experimental class using PBL assisted by audiovisual media and those in the control class using the conventional model, with pretest mean scores of 56.61 and 55.18, respectively. However, the hypothesis test results on posttest data showed a significant difference, with the posttest mean score of the experimental class reaching 78.39, higher than the control class's posttest mean score of 70.00. Thus, the use of the PBL model assisted by audiovisual media has been proven to have a positive impact on improving students' critical thinking skills.